Modeling and stress analysis of aluminium alloy based composite pressure vessel through ANSYS software. (2021) - Mohanavel, V.; Prasath, S.; Arunkumar, M.; Pradeep, G.M.; Surendra Babu, S.
Abstract: The traditional materials based pressure vessels are having more strength. Due to their high weight to strength ratio and corrosive properties, but it is not suitable in the aerospace and oil and gas factories. In industries are extensively required for pressure vessels, which will have low weight to strength ratio without affecting the strength. In recent years, most of the sectors replace conventional materials with aluminum matrix composite materials. On the other hand, Aluminum matrix composite (AMCs) materials with their higher specific strength and these characteristics will reduce the structure's weight. In this research paper, the AA6082 alloy based aluminum matrix composites have been prepared by stir casting technique to test their mechanical properties under different weight percentages of reinforcement. Various mechanical studies have been done, such as tensile, impact, flexural, and hardness. For the same geometrical parameters of the steel pressure vessel, FE Analysis of AMCs composite pressure vessel is carried out, and stresses for different internal pressures are determined. And the design is carried out in design software solid works and analyze in ANSYS workbench. Then the results of steel pressure vessel and composite pressure vessel are compared for stress results.